Upshifting the Ipsilateral Proximal Femur May Provide Satisfactory Reconstruction of Periacetabular Pelvic Bone Defects After Tumor Resection. Issue 9 (September 2018) - Lin, Nong; Li, Hengyuan; Li, Weixu; Huang, Xin; Liu, Meng; Yan, Xiaobo; Pan, Weibo; Yang, Disheng; Ye, Zhaoming
Abstract: Background: Pelvic ring reconstruction after resection of pelvic malignancies or aggressive benign tumors remains challenging, especially when the tumor invades periacetabular bone, resulting in a Type II resection as classified by Enneking and Dunham (removal of part or all of the acetabulum). Although numerous treatment approaches are in use, none is clearly superior to the others. An alternative involving use of the ipsilateral proximal femur as an autograft has not been well characterized, so we present our preliminary experience with this approach. Questions/purposes: (1) What were the oncologic outcomes after using an ipsilateral proximal femur autograft for reconstruction after Type II pelvic resection in a small series of patients who underwent this reconstructive approach? (2) What were the Musculoskeletal Tumor Society (MSTS) scores after this reconstruction? (3) What complications were observed? Methods: Between October 2006 and May 2016, we treated 67 patients with Type II malignant or aggressive benign tumors of the ilium. Of those, we used an ipsilateral proximal femur and a prosthesis as a reconstruction method for 11 patients with pelvic tumors. In general, we performed this approach in young or middle-aged patients with primary malignant or aggressive benign tumors involving pelvic area II and in whom the tumor did not invade the hip. The method used for resection of pelvic tumors included osteotomy of the femoral shaft, harvesting the proximal femur as a graft. The length of the femoral graft was determined by the extent of the pelvic defect. The proper placement was selected after a comparison of the proximal femur and the pelvic defect. A curved reconstruction plate and cancellous bone screws were used for pelvic fixation. The operative duration and total blood loss were recorded. Of the 11 patients who underwent this approach, all but one had at least 2 years of followup unless death occurred earlier, and all but one have been seen within the last year for evaluation. Functional outcomes were assessed using the MSTS scoring system. Local recurrence, metastases, and deaths were recorded as were complications including infection, bone nonunion, mechanical failure and sciatic nerve palsy. Results: The followup was a mean of 37 months (range, 13-96 months). One patient was lost to followup. Three patients died of disease owing to local recurrence or lung metastasis. The other seven patients lived without evidence of tumor. The main complications included mechanical failure in two patients, nonunion in one patient, infection in two patients, and sciatic nerve palsy in one patient. The median MSTS function score was 70% (21 of 30 points; range, 11-25 points). Conclusions: Our preliminary results show that this technique of using the ipsilateral proximal femur may be an alternative method for reconstruction of pelvic bone defects after tumor resection. Even with this short followup, complications were common, but short-term function appears to be comparable to studies of other options. Longer term followup with more patients is necessary to confirm our results. Level of Evidence: Level IV, therapeutic study.